The South China Sea Disputes: Is High Politics Overtaking?. (11th April 2013) - Karim, Mohd Aminul
<x xml:space="preserve">Abstract</x> The aim of this article is to examine the implications of high politics in the South China Sea disputes, which basically involve the United States, and other claimant countries, such as Vietnam and the Philippines on one side, and China on the other. The two main actors, namely China and the United States, appear to be re‐assertive. All the claimant countries are asking for their stakes, which involve their sovereignty, and sovereign and maritime rights. The fall‐out is the polarization of the stakeholders and greater military build‐up. Overt military confrontation is a remote possibility at the moment, mainly because of overriding considerations, such as interdependence in economy and a trend towards regionalism. Nevertheless, the array of sophisticated military forces and the vital national interests of the stakeholders in the Sea tend to portend a problematic frontier. This article indicates certain policy implications and attempts to develop the framework of a scenario that is likely to emerge premised on high politics.